Keanekaragaman spesies avifauna di KHDTK Hambala, Nusa Tenggara Timur - Oki Hidayat (Foresty Faculty of Hasanuddin University, 2013)
Special-Purposed Forest (also known as Kawasan Hutan Dengan Tujuan Khusus/KHDTK) Hambala is defined as forest area for research and development, education and training. Unfortunately, its potency has not been known completely. One of the biodiversity potencies in this area is avifauna. Population and avifauna diversity can be used to measure the development’s sustainability. Therefore, avifauna is accepted as a key indicator of the health of the environment and overall biodiversity situation. This study was aimed to get information about the diversity of avifauna and their abundance in KHDTK Hambala. The research conducted with encounter rates method, the random exploration was done three times at morning and afternoon. The results showed that KHDTK Hambala has high species diversity with diversity index value of 3.06. Thirty six species from 24 families were encountered during the study. About 11% (4 species) bird is abundance, 39% (14 species) bird is common, 19% (7 species) bird is frequent, 6% (2 species) bird is uncommon, and 25% (9 species) bird is rare.